Designing relational database structures for storing and processing language questionnaire data: Example from a study in dictionary use - Lew, Robert (Łódź University Press, 2003)
The author discusses a methodological approach to storing, structuring, and processing complex data a large-scale dictionary use study.
Keywords: database; questionnaire; dictionary use; lexicography; dictionaries; dictionary preference; information in dictionaries; dictionary entry structure; dictionary definition; dictionary equivalent